Assessment of physicochemical properties and comparison of the dissolution profile of amoxicillin caplets - Een Widiyasari; Teuku Nanda Saifullah Sulaiman (Universitas Islam Indonesia, 2020)
Background: Marketed drugs must meet the required standards to guarantee product quality. Amoxicillin is a generic compound marketed under various trademarks as copy drugs. Amoxicillin caplets are an immediate release dosage form of BCS class I. An essential aspect of evaluating copy drugs is to assess the equivalence for their treatment to the innovator drugs to ensure the safety and effectiveness of the circulating copy drugs.Objective: The study aims to evaluate the physicochemical properties and compare the dissolution profile of amoxicillin caplets available in the market.Methods: Five amoxicillin caplet products, four test products, and one reference product were tested for their physicochemical properties and dissolution. The dissolution test was carried out with a type II device at a speed of 75 rpm in 900 mL of media buffered at pH 1.2, 4.5, and 6.8 and at a temperature of 37 +/- 0.5degrees celcius. The dissolution profile was analyzed by comparing it with the similarity factor (f2) parameters.Results: Two of the four amoxicillin caplet products had a similar dissolution profile to the reference products, namely products A and B. Products C and D were dissimilar because f2 was lower than 50 at pH 4.5. The caplets tested had almost the same dimensions, and all caplets met the requirements for uniformity of content, hardness, disintegration time, and dissolution.Conclusion: Not all of the amoxicillin caplets in the market have a similar dissolution profile to the reference products. Keywords: caplets, amoxicillin, dissolution, similarity factor Intisari Latar belakang: Sediaaan obat yang dipasarkan harus memenuhi standar yang ditetapkan untuk menjamin kualitas produk. Amoksisilin merupakan senyawa generik, dipasarkan dengan berbagai merek dagang yang merupakan obat copy. Kaplet amoksisilin merupakan sediaan dengan pelepasan segera yang termasuk dalam BCS kelas I. Komponen penting dalam mengevaluasi obat copy yaitu menilai kesetaraan terapinya terhadap obat inovator sehingga dapat menjamin bahwa obat copy yang beredar aman dan efektif. Tujuan: Penelitian ini bertujuan untuk mengevaluasi sifat fisika kimia dan uji disolusi terbandingkan sediaan kaplet amoksisilin yang beredar dipasaran.Metode: Sebanyak 5 produk kaplet amoksisilin, 4 produk uji dan 1 produk pembanding diuji sifat fisika kimia dan disolusinya. Uji disolusi dilakukan dengan alat tipe II dengan kecepatan 75 rpm dalam 900 mL media yang dibuffer pada pH 1,2; 4,5; dan 6,8 dan suhu 37 +/- 0,5derajat celcius. Profil disolusi dianalisis dengan membandingkan profil disolusi dengan parameter similiarity factor (f2).Hasil: Hasil penelitian menunjukkan 2 produk dari 4 produk kaplet amoksisilin memiliki kemiripan profil disolusi terhadap produk pembanding yaitu produk A dan B, sementara 2 produk yang lain tidak memiliki kemiripan karena nilai f2 kurang dari sama dengan 50 pada pH 4,5 (produk C dan D). Kaplet yang diuji memiliki dimensi yang hampir sama, semua kaplet memenuhi persyaratan keseragaman sediaan, kekerasan, waktu hancur dan disolusi.Kesimpulan: Kaplet amoksisilin yang beredar tidak semuanya memiliki kemiripan profil disolusi dibandingkan produk pembanding. Kata kunci : kaplet, amoksisilin, disolusi, similiarity factor